University social commitment in achieving inclusive health systems - Cruz Xiomara Peraza de Aparicio; Odalys del Carmen Toledo Rodríguez; Tania Fonseca Borges (Medisur)
Universities are privileged to provide with innovative solutions certain social demands, among which, health has an important place. Social exclusion is a process in which different factors take part and to which health systems are included, with specificities for each region and country. This work has the objective to base the social order of the University in the achievement of inclusive health systems, with emphasis in the case of the Metropolitan University of Ecuador. Some of the strategies developed by different organizations worldwide, related to the subject are discussed; as well as several actions developed by said university in this sense, as a sample of what, can be done to contribute to this social claim from the educational scenarios.